School value-added and long-term student outcomes - Lars J. Kirkebøen (University of Oslo, Department of Economics, 2021)
This paper studies school quality in the context of Norwegian compulsory schooling. I demonstrate that even when lagged achievement is not observed, it is possible to construct informative value-added (VA) indicators of persistent school quality by adjusting exam scores for students' background characteristics. These VA indicators show little bias forecasting average exam performance out of sample, and are also predicative of long-term student outcomes, including earnings. Three quasi-experiments using variation from student mobility and changes in neighborhood school assignments indicate that the differences captured by the VA indicators do indeed reflect differences in school quality, rather than unobserved student characteristics. The finding help connect learning outcomes with later labor market outcomes, e.g. for cost-benefit analysis of interventions in schools.
Keywords: J24; I2; 330; School quality; value-added; VAM; earnings